1994
DOI: 10.1111/j.1432-1033.1994.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Protein Import

Abstract: Proteins have to be at least partially unfolded upon passage through the biological membranes. Previous studies with a dihydrofolate reductase fusion protein containing a chloroplast transit peptide showed that stabilization of the tertiary structure of the fusion protein by binding of a ligand, methotrexate, failed to block its translocation across the envelopes, suggesting that chloroplast envelopes have strong activity to unfold proteins [America, T., Hageman, J., Guéra, A., Rook, F., Archer, K., Keegstra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…Schnell and Blobel (1993) Endo et al (1994) found that a full-~l ength PC molecule was halted in its transfer across the thylakoid membrane by the presence of a DHFR-B. OE17-BPTI MTX C-terminal domain, this protein is transported via the so-called Sec-related pathway and likely traverses the membrane through a pore similar to the -I 20-60-A channel formed by Sec6lp (Hamman and Johnson, 1996;Hanein et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schnell and Blobel (1993) Endo et al (1994) found that a full-~l ength PC molecule was halted in its transfer across the thylakoid membrane by the presence of a DHFR-B. OE17-BPTI MTX C-terminal domain, this protein is transported via the so-called Sec-related pathway and likely traverses the membrane through a pore similar to the -I 20-60-A channel formed by Sec6lp (Hamman and Johnson, 1996;Hanein et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Endo et al (1994) showed that a C-terminal MTX-bound DHFR domain can halt the translocation of PC on the Sec-related thylakoid pathway. However, no arrested translocation intermediates have yet been generated in the ApH-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting mRNA was translated in a wheat germ extract (Promega) at 258C for 2 h in the presence of [ 35 S]Met. A plasmid for the in vitro expression of pSSU-DHFR, which consists of the full-length precursor to SSU fused to the entire mouse dihydrofolate reductase, was constructed by inserting the pSSU coding sequence lacking the stop codon into pPC-DHFR/SP (Endo et al, 1994) at a PstI/BamHI site. The fusion protein pSSU-DHFR was synthesized using TNT SP6-coupled reticulocyte lysate system (Promega) at 308C for 90 min in the presence of [ 35 S]Met.…”
Section: In Vitro Transcription and Translation Of Preproteinsmentioning
confidence: 99%
“…Furthermore, the binding constant of methotrexate to DHFR is lower than that of Ni 2+ to (His)6. Eventually the unfolding capacity of the chloroplast envelope membrane [8,9] is able to discriminate between the two binding constants, thereby explaining why the import of (His)6-containing precursor protein is inhibited by Ni 24 , while DHFR fusion proteins are still imported in the presence of methotrexate. To further investigate this point we currently produce a precursor fusion protein with two C-terminal additions: a DHFR sequence followed by a hexahistidyl peptide.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand the import of a transit peptide-DHFR fusion protein is not blocked by the presence of methotrexate in higher plants, pointing to a strong unfolding activity associated with chloroplast envelope membranes [7,8]. Also the protease sensitivity of a chimeric precursor protein containing the ricin A chain, when bound to chloroplasts, points to an unfolding activity of the chloroplast envelope [9].…”
Section: Introductionmentioning
confidence: 99%